Quality assessment of hydroquinone, mercury, and arsenic in skin-lightening cosmetics marketed in Ilorin, Nigeria - Olasunkanmi David Bamidele; Blessing Ayomide Kayode; Oluwasegun Ibrahim Eniayewu; Adebanjo Jonathan Adegbola; Raphael Segun Olatoye; Ngaitad Stanislaus Njinga; Sa’ad Toyin Abdullahi; Moji Taibat Bakare-Odunola (Scientific Reports, 2023)
Abstract Hydroquinone, Mercury (Hg), and Arsenic (As) are hazardous to health upon long-term exposure. Hydroquinone, Hg, and As were analysed in skin-lightening cosmetics randomly purchased from different cosmetic outlets within the Ilorin metropolis, Nigeria. The amount of hydroquinone in the samples was determined using a UV-spectrophotometry method at 290 nm. Hg and As were quantified using atomic absorption spectrophotometry (AAS). UV-spectrophotometry method validation showed excellent linearity (r2 = 0.9993), with limits of detection (0.75 µg/mL), limits of quantification (2.28 µg/mL), relative standard deviation (0.01–0.35%), and recovery (95.85–103.56%) in the concentration range of 5–50 µg/mL. Similarly, r2, LOD, and LOQ for Hg and As were 0.9983 and 0.9991, (0.5 and 1.0 µg/L) and 1.65 and 3.3 µg/L) respectively. All the samples contained hydroquinone, Hg and As in varying amounts. The amounts of hydroquinone, Hg and As present were in the ranges of 1.9–3.3%, 0.08–2.52 µg/g and 0.07–5.30 µg/g respectively. Only three of the analysed samples contained hydroquinone within the permissible limit of 2.0% w/w in cosmetic products. All the samples analysed contained mercury and arsenic in varying amounts. The need to periodically monitor the levels of hydroquinone, mercury, and arsenic in skin-lightening cosmetics marketed in Nigeria is recommended.